A Content Analysis of English Textbook “Bright An English” Used in Second Grade Junior High School Based on Merdeka Curriculum - Nurhayati Tuluki; Harni Jusuf; La aba; Andi Nurwati; Enni Akhmad (English Education Department, 2025)
In the context of educational reform in Indonesia, the implementation of the Merdeka Curriculum has brought significant changes over the past few decades. A crucial aspect of this transformation is the curriculum for students, aimed at equipping them with the knowledge and skills necessary to become productive members of society. Launched by the Ministry of Education in 2020, the Merdeka Curriculum emphasizes a more holistic and inclusive educational approach, focusing on student-centered learning and technology use. This study aims to analyze the alignment of the textbook